A large sized megalosaurid (Theropoda, Tetanurae) from the late Jurassic of Uruguay and Tanzania. (March 2020) - Soto, Matías; Toriño, Pablo; Perea, Daniel
Abstract: We report the first Jurassic remains that can confidently be referred to a megalosaurine theropod in Uruguay and Tanzania. This identification is sustained on a detailed morphological study. The large size of both teeth (>70 mm in lateral teeth) and denticles (<7 denticles per 5 mm), the clearly visible braided enamel texture, the centrally placed and apically restricted mesial carina in mesial teeth, and general shape of the teeth strongly resembles Torvosaurus . This is coherent with multivariate analyses of two datasets of large theropod teeth measurements, and also with the results of a phylogenetic analysis of theropod teeth. The presence of Torvosaurus in the Tacuarembó Formation of Uruguay further strengthens the Late Jurassic age proposed for the fossiliferous horizon. The Uruguayan megalosaurid would represent the apex predator in the vertebrate assemblage. The occurrence of megalosaurids in the Late Jurassic of Uruguay (the first unquestionable megalosaurid from South America) and Tanzania also greatly expands the geographical range of the family. Graphical abstract: Image 1 Highlights: We describe a large theropod from Uruguay represented by isolated teeth. Detailed morphological analysis strongly resembles the megalosaurine Torvosaurus . Multivariate and phylogenetic analyses support this referral. We propose that the enigmatic ' Megalosaurus ' ingens from Tanzania should also be referred to Torvosaurus .